The Effectiveness on the Use of Constructivism-Based Vector Analysis Module for 4th Semester Students in Department of Mathematics Education UNRIKA in Academic Year Of 2016/2017 - Nailul Himmi; Asmaul Husna (UIR PRESS, 2018)
Based on the observations on the students in department of Mathematics Education UNRIKA, especially in Vector Analysis course, it is found that the students find it difficult to understand the material. This study aimed at knowing the effectiveness on the use of constructivism-based vector analysis module. The research design was using one shoot case study. The research population was 41 students with saturated sampling technique. The research instrument was using essay test consisting of five questions that hadtested its validity and reliablity. The hypothesis testing was using one sample T-test assisted with SPSS Statistics 20.0 in the significant level of 5%. Based on the analysis results, it was obtained sig (0.007) < α (0.05), so it can be concluded that the use of constructive-based vector analysis module to wards the learning outcomes for 4th semester students in department of Mathematics Education UNRIKA in academic year of 2016/2017 can be categorized as moderate.